Penataran Pekerja Arsitektur Tradisional Bali di Desa Pakraman Bedha Kabupaten Tabanan - A.A.A.O. Saraswati; I W. Kastawan; W. Widiastuti; E.E. Moniaga (Buletin Udayana Mengabdi, 2016)
Human resources (HR) is one of the resources - assets and capital function in maintaining the continuity of Balinese traditional architecture (ATB) to realize the existence of the ATB.The ability of ATB workers tend to be degraded to sustain ATB.Workers tend to follow the wishes of the buyer, which emphasizes on the principles of aesthetics. With these capabilities, the produced in the form of architecture with ‘ornamented structure’which do not apply the principles of earthquake-resistant architecture. Upgrading of workers is an act of preservation of cultural values, consistently through Udayana Dedicate Grant - Udayana University. Upgrading ATB workers in Bedha Pakraman Village done through a workshop- training of workers ATB for improve understanding the principles of earthquake resistance on ATB. Furthermore, by way of word of mouth conducted by ATB workers, is expected not long after there will be an increase in the entire HR worker ATB in the village of Bedha Pakaraman. Outcomes of this upgrading are ATB workers who can produce sketch of parts of the structure of the ATB that resistant to earthquakes.